"Our ideas are already governing." The think tank Ideas Republicanas in the strategy of the radical right in Chile. - Morales, Juan Jesús (2024)
Specialized literature has paid attention to the emergence in recent years of the radical right in Chile, represented mainly by the Partido Republicano. However, it has not studied the place that Ideas Republicanas occupies in this party to install ideas and discourses in Chilean society. For this reason, the objective of this article is twofold. First of all, the most representative ideas and speeches that it disseminates are analyzed. Secondly, we discuss what type of partisan think tank it is, categorizing it and examining some of its main functions. To achieve these two objectives, a qualitative methodology was carried out based on the case study and which involved an exhaustive analysis of reports prepared by Ideas Republicanas. In addition, the categories and subcategories of analysis were triangulated with speeches from the Ruta Republicana manifesto. Secondary sources were also used, such as interviews and news, from two national newspapers. This analysis made it possible to raise categories that contribute to the theorization of the radical right in Chile. It is concluded that Ideas Republicanas is a completely atypical partisan think tank as it is a center highly characterized by the cultural battle.